Preparation of Novel Mesoporous LaFeO3-SBA-15-CTA Support for Syngas Formation of Dry Reforming - Luming Li; Song Wu; Hongmei Li; Jie Deng; Junshan Li (Nanomaterials, 2022)
A nanocomposite NiPt/5LSBA-160 catalyst comprised of highly dispersed Ni nanoparticles contacting intimately with Pt over novel mesoporous LaFeO3-SBA-15-CTA support with a high specific surface area (SSA) was successfully developed for the dry reforming of methane. Results revealed that the high SSA mesoporous LaFeO3-SBA-15-CTA materials could first be synthesized by an in situ growth hydrothermal process and used as an excellent carrier candidate of Ni-based catalysts to achieve enhanced catalytic activity due to the strong interaction between LaFeO3 and Ni species. Moreover, the introduction of Pt over a Ni/5LSBA-160 catalyst would further promote the interaction between Ni and support, improve the dispersion of active Ni centers and obtain a higher syngas formation rate as well as tolerance to carbon coking than that of a Pt-free Ni/5LSBA-160 catalyst sample. This finding uncovers a promising prospect for high SSA mesoporous perovskite preparation and utilization in catalysis such as oxidation, hydrogenation, photocatalysis, energy conversion and so on.